A construção da identidade quilombola da Comunidade de Braço Forte - Salto da Divisa / Minas Gerais : o processo de luta, mobilização e defesa - Reginaldo Cordeiro dos Santos Junior (2018)
The effort undertaken in this research was to ethnograph the community strategies of the quilombo of Braço Forte - located in the municipality of Salto da Divisa, Minas Gerais - with regard to the judicial battle, held since 2015, when the group reoccupied / resumed its traditional territory. Their ancestors were enslaved and expropriated of their territory in centuries XIX and XX by a family of farmers of the region. The braçofortenses were compulsorily living in the periurban region of Salto da Divisa and there they adapted, guaranteeing the maintenance of life with the artisanal fishing, washing of clothes in a traditional way in the slabs of the river, extraction of stones for crafts and construction, among others activities. In 1997, the braçofortenses are again expropriated, hit by the dam created by the Itapebi Hydroelectric Power Plant, located in the neighboring municipality, Itapebi - Bahia State. Protagonists of a history permeated by challenges and risks, the braçofortenses have since started a process of struggle, mobilization for their recognition as a quilombola community and defense for their traditional territory.